2013
DOI: 10.1016/j.cell.2013.06.026
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Antagonism Regulates Breast Cancer Stemness and Metastasis via TET-Family-Dependent Chromatin Remodeling

Abstract: SUMMARY Tumor cells metastasize to distant organs through genetic and epigenetic alterations, including changes in microRNA (miR) expression. Here we find miR-22 triggers epithelial-mesenchymal transition (EMT), enhances invasiveness and promotes metastasis in mouse xenografts. In a conditional mammary gland-specific transgenic (TG) mouse model, we show that miR-22 enhances mammary gland side-branching, expands the stem cell compartment, and promotes tumor development. Critically, miR-22 promotes aggressive me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
389
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(412 citation statements)
references
References 75 publications
20
389
1
2
Order By: Relevance
“…They also demonstrated that miR-22 induced metastatic potential by silencing miR-200 through the targeting of ten-eleven translocation proteins, which are a family of methylcytosine dioxygenases. 131 Moreover, Park et al 132 showed that these miRNA cooperatively regulated the expression of the E-cadherin transcriptional repressors ZEB1 and ZEB2, which have previously been implicated in EMT and tumor metastasis. Jiang et al reported that miR-29 mediated EMT and promoted metastasis in breast cancer.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…They also demonstrated that miR-22 induced metastatic potential by silencing miR-200 through the targeting of ten-eleven translocation proteins, which are a family of methylcytosine dioxygenases. 131 Moreover, Park et al 132 showed that these miRNA cooperatively regulated the expression of the E-cadherin transcriptional repressors ZEB1 and ZEB2, which have previously been implicated in EMT and tumor metastasis. Jiang et al reported that miR-29 mediated EMT and promoted metastasis in breast cancer.…”
Section: Mirna In Triple-negative Breast Cancermentioning
confidence: 99%
“…miR-22 acted as a crucial epigenetic modifier and promoter of EMT and breast cancer stemness toward metastasis by silencing anti-metastatic miR-200. This was accomplished through direct targeting of the ten-eleven translocation family that modifies DNA by hydroxylating 5-methylcytosine (Song et al 2013). MicroRNAs have been recognized as critical regulators of EMT and CSCs.…”
Section: Downregulation Of Specific Micrornasmentioning
confidence: 99%
“…promoter [33]. However, the mechanism by which this epigenetic mark of 5-hmC and the related enzyme of TET participate in IPF progression remains unknown.…”
Section: Discussionmentioning
confidence: 99%